Tyrosine Is Associated with Insulin Resistance in Longitudinal Metabolomic Profiling of Obese Children. (21st December 2015) - Hellmuth, Christian; Kirchberg, Franca Fabiana; Lass, Nina; Harder, Ulrike; Peissner, Wolfgang; Koletzko, Berthold; Reinehr, Thomas
Abstract : In obese children, hyperinsulinaemia induces adverse metabolic consequences related to the risk of cardiovascular and other disorders. Branched-chain amino acids (BCAA) and acylcarnitines (Carn), involved in amino acid (AA) degradation, were linked to obesity-associated insulin resistance, but these associations yet have not been studied longitudinally in obese children. We studied 80 obese children before and after a one-year lifestyle intervention programme inducing substantial weight loss >0.5 BMI standard deviation scores in 40 children and no weight loss in another 40 children. At baseline and after the 1-year intervention, we assessed insulin resistance (HOMA index), fasting glucose, HbA1c, 2 h glucose in an oral glucose tolerance test, AA, and Carn. BMI adjusted metabolite levels were associated with clinical markers at baseline and after intervention, and changes with the intervention period were evaluated. Only tyrosine was significantly associated with HOMA (p < 0.05 ) at baseline and end and with change during the intervention (p < 0.05 ). In contrast, ratios depicting BCAA metabolism were negatively associated with HOMA at baseline (p < 0.05 ), but not in the longitudinal profiling. Stratified analysis revealed that the children with substantial weight loss drove this association. We conclude that tyrosine alterations in association with insulin resistance precede alteration in BCAA metabolism. This trial is registered with ClinicalTrials.gov IdentifierNCT00435734 .